Psychological Predictors of Health-Related Quality of Life Among Women With Polycystic Ovary Syndrome in Rivers State - Enyelunekpo R. Roberts; Keyna C. George; Esther James; Emmanuel E. Uye (International Journal of Business and Quality Research, 2026)
The prevalence of polycystic ovary syndrome (PCOS) has significant implications on women's health-related quality of life (HRQoL). While the physical aspects of PCOS on HRQoL have been widely studied, studies linking psychological predictors of HRQoL among women with PCOS in Rivers State have received little investigation. Therefore, this study examines the predictive ability of psychological distress, anxiety, depression and stress on HRQoL among women diagnosed with PCOS in Rivers State, Nigeria. The study adopted cross-sectional survey design while purposive sampling technique was used to select the study population. Data were conveniently collected from 206 participants using validated scales and analyzed using multiple regression analysis to test five hypotheses which were accepted at p <.001 of significance. The results show that psychological distress, anxiety, depression and stress jointly predicted HRQoL among women diagnosed with PCOS (R2 = .777, F(4, 202) = 174.780, p<.001). Furthermore, psychological distress, R2= .748, F(1,204) = 605.644, p <.001; depression, R2 = .461, F(1,204) =174.289, p <.001; anxiety, R2 = .507, F(1,204) = 210.133, p <.001, and stress, R2 = .551, F(1,204) = 250.086, p<.001 independently predicted HRQoL among study participants. The study comes as the first among this population and sample. The study recommends government agencies, healthcare providers and other stakeholders to combine gynecological, psychological and lifestyle management strategies to support women diagnosed with PCOS in order to improve their HRQoL.